Companies act 2016: the game changer - Mohd. Sulaiman, Aiman @ Nariman; Abd. Aziz, Nor Azimah; Shih, Lee; Vooi, Andrew Chiew Ean (2016)
The Companies Act 2016 is expected to transform the business regulatory landscape in Malaysia, facilitating business and investment and reinvigorating growth and prosperity. As partners and advisors to business, government and society, all accountants are encouraged to attend this technical session which introduces the new bills and explains their impact on business models and processes and future economic growth.